PAX6: 25th anniversary and more to learn. (March 2017) - Cvekl, Ales; Callaerts, Patrick
Abstract: The DNA-binding transcription factor PAX6 was cloned 25 years ago by multiple teams pursuing identification of human and mouse eye disease causing genes, cloning vertebrate homologues of pattern-forming regulatory genes identified in Drosophila, or abundant eye-specific transcripts. Since its discovery in 1991, genetic, cellular, molecular and evolutionary studies on Pax6 mushroomed in the mid 1990s leading to the transformative thinking regarding the genetic program orchestrating both early and late stages of eye morphogenesis as well as the origin and evolution of diverse visual systems. Since Pax6 is also expressed outside of the eye, namely in the central nervous system and pancreas, a number of important insights into the development and function of these organs have been amassed. In most recent years, genome-wide technologies utilizing massively parallel DNA sequencing have begun to provide unbiased insights into the regulatory hierarchies of specification, determination and differentiation of ocular cells and neurogenesis in general. This review is focused on major advancements in studies on mammalian eye development driven by studies of Pax6 genes in model organisms and future challenges to harness the technology-driven opportunities to reconstruct, step-by-step, the transition from naïve ectoderm, neuroepithelium and periocular mesenchyme/neural crest cells into the three-dimensional architecture of the eye.